Neural Activity Correlates With Behavior Effects of Anti-Seizure Drugs Efficacy Using the Zebrafish Pentylenetetrazol Seizure Model - Milder, Patrick C.; Zybura, Agnes S.; Cummins, Theodore R.; Marrs, James A. (Frontiers in Pharmacology, 2022)
Approximately 30% of patients with epilepsy do not achieve adequate seizure control through current anti-seizure drugs and treatment methods. Therefore, a critical need exists to efficiently screen anti-seizure drugs to enhance our ability to tailor treatment protocols and improve patient outcomes. The zebrafish pentylenetetrazol (PTZ) seizure model has become an increasingly popular screening paradigm for novel anti-seizure compounds. However, previous research using this model was variable due to differing experimental methods. Here, we present a method that was optimized to improve reliability and reproducibility in our laboratory using this PTZ model to develop a more robust screening of anti-seizure drugs comparing behavior and neural activity. Our behavior assay, spanning 90 minutes using 10 mM PTZ on 7 days post fertilization zebrafish, provides a broad window to observe anti-seizure drug efficacy. To compare our method with previously published data, we tested carbamazepine, lamotrigine, and topiramate, which have been tested in previous PTZ zebrafish assays. In addition, we assessed the candidate anti-seizure compound GS967, which has not been previously tested in the zebrafish seizure model. We examined the efficacy of anti-seizure drugs by acute administration concurrent with PTZ application and by pretreatment prior to exposure with PTZ. Pretreatment permitted us to examine potential neuroprotection and determine whether treatment time affects anti-seizure drugs’ responses. As independent validation of anti-seizure drugs’ effects, we evaluated whether the anti-seizure drug efficacy in the behavioral assay correlated with neural activity measurements, using electroencephalogram (EEG) and calcium signaling using GCaMP. There was no significant difference in the reduction of PTZ-induced seizure behavior activity between the pretreatment groups and acute treatment groups. Acute treatment with anti-seizure drugs in the EEG and GCaMP assays from 15 to 30 minutes post-anti-seizure drug exposure revealed consistent results between behavioral, EEG, and GCaMP assays for two of the three anti-seizure drugs. Lamotrigine only reduced neural activity (EEG and GCaMP assays). Carbamazepine, topiramate, and GS967 reduced activity in all three assays. The findings show that EEG and GCaMP assays largely correlate with the behavior findings, helping us connect physiological and behavior responses to anti-seizure drug and better assess anti-seizure drug efficacy.